Comparative Analysis of the Complete Mitochondrial Genomes for Development Application - Alexander Kenechukwu, Nwobodo; Li, Man; An, Lei; Cui, Miaomiao; Wang, Cailin; Wang, Aili; Chen, Yulin; Du, Saijun; Feng, Chenyao; Zhong, Sijin; Gao, Yuying; Cao, Xueyan; et al. (Frontiers in Genetics, 2019)
This present research work reports the comparative analysis of the entire nucleotide sequence of mitochondrial genomes of Serranochromis robustus and Buccochromis nototaenia and phylogenetic analyses of their protein-coding genes in order to establish their phylogenetic relationship within Cichlids. The mitochondrial genomes of S. robustus and B. nototaenia are 16,583 and 16,580 base pairs long respectively, including 13 protein-coding genes (PCGs), 2 ribosomal RNA genes, 22 transfer RNA genes and one control region (D-loop) which is 888 and 887 base pairs long respectively, showing the same gene order and identical number of gene or regions with other well elucidated mitogenomes of Cichlids. However, with exception of cytochrome-c oxidase subunit-1 (COX-1) gene, all the identified PCGs were initiated by ATG-codons. Structurally, eleven tRNA genes in B. nototaenia species and nine tRNA genes in S. robustus species, folded into typical clover-leaf secondary structure created by the regions of self-complementarity within tRNA. All the 22 tRNA genes in both species lack variable loop. Moreover, 28 genes which include 12-protein-coding genes are encoded on the H-strand and the remaining 9 genes including one protein-coding gene are encoded on the L-strand. Thirteen sequences of concatenated mitochondrial protein-coding genes were aligned using MUSCLE, and the phylogenetic analyses performed using maximum likelihood and Bayesian inference showed that S. robustus and B. nototaenia had a broad phylogenetic relationship. These results may be a useful tool in resolving higher-level relationships in organisms and a useful dataset for studying the evolution of the Cichlidae mitochondrial genome, since Cichlids are well-known model species in the study of evolutionary biology, because of their extreme morphological, biogeographical, parental care behavior for eggs and larvae and phylogenetic diversities.